1976
DOI: 10.1021/i160059a004
|View full text |Cite
|
Sign up to set email alerts
|

Controllability of Process Systems. Application of Harriott's Index of Controllability

Abstract: parallel lines are observed in Figure 9 for the values of Hf" of the hydrates of MgC1:; and FeC13. We assume, therefore, that the same relation also holds for the values of Gf" of the hydrates of MgCl2 and FeC13. Since Gf" for FeC13 is known, we are now able to calculate Gf" for the hydrates of FeC13. If data for Hf" and Gf" of other metal chlorides (e.g. BaC12, CaC12, and NiC12) and their hydrates are used as a basis of the analogy, the same results are obtained quantitatively. A plot of the values of Gf" (Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The slope of the plot, which equals - Frequency domain techniques are similar to those in the Laplace domain and require the selection of a suitable range of ω values in deriving the relevant parameters from the transient responses. Jeffreson (1970) suggested that the parameter fitting should be carried out over the range of frequencies decided by 0<ωΤ<1, as the higher order terms in eqs(77, 78) would make a negligible contribution to the summation over the smaller frequency range. If such a range is used, the frequency response will yield parameters identical to the time domain moment analysis, provided that the experimental data actually fit the proposed model, thus indicating model validity.…”
Section: Methods Bymentioning
confidence: 99%
See 2 more Smart Citations
“…The slope of the plot, which equals - Frequency domain techniques are similar to those in the Laplace domain and require the selection of a suitable range of ω values in deriving the relevant parameters from the transient responses. Jeffreson (1970) suggested that the parameter fitting should be carried out over the range of frequencies decided by 0<ωΤ<1, as the higher order terms in eqs(77, 78) would make a negligible contribution to the summation over the smaller frequency range. If such a range is used, the frequency response will yield parameters identical to the time domain moment analysis, provided that the experimental data actually fit the proposed model, thus indicating model validity.…”
Section: Methods Bymentioning
confidence: 99%
“…Included in Table 18 are the final results of the regression analysis using an appropriate range of ω as suggested by Jeffreson (1970) (i.e., 0<ωΤ<1) in the frequency domain methods for the experimental data set of Purves and Larson (1980). The amplitude ratio for this data set is little over unity in the vicinity of ω -* 0, so the gradients yielded negative values, resulting in unrealistic parameters (results in regression analysis of eqs(81-82)).…”
Section: 33 Methods Bymentioning
confidence: 99%
See 1 more Smart Citation
“…Accounting for the effects of both Kmax and coc, Harriott concludes the IAE is inversely proportional to their product. In a recent paper, Jeffreson (1976) investigated the relationship between this index and three commonly used indices of closed-loop system performance for several process models.…”
Section: Introductionmentioning
confidence: 99%
“…The inverse, P™1 (or 7_1 where 7 = cvc(l + Khma/2)), is approximately proportional to the optimum integral absolute error following a step disturbance. The significance of the result, investigated in some detail by Jeffreson (1976), is that an approximate figure of merit or performance index may be assigned not only to the usual firstorder-lag system with dead time but also to systems consisting of any combination of lag time constants with or without dead time subject to certain limitations outlined in the paper. It follows that if the process dynamics of the plant are known in detail, the optimal performance achievable under feedback control may be estimated assuming proportional integral control.…”
Section: Empirical Performance Index Of Harriottmentioning
confidence: 99%